Characteristics of Islamic Educational Counseling - Hadini, Hadini; Imanuddin, M.; Akhir, Nur Afzan Binti Md; Harmonedi, Harmonedi (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2025)
Various psychological problems that arise in the world of Islamic education require a counseling approach that is not only psychological, but also spiritual. This study aims to identify and analyze the characteristics of Islamic Educational Counseling that distinguish it from general counseling by tracing its theological basis based on the Qur'an and hadith. The method used in this study is library research, by collecting and reviewing various literature in the form of books, scientific journals, and previous research results that are relevant to the topic of Islamic Educational Counseling. The results of the study show that Islamic Educational Counseling has two main characteristics: first, the implementation of counseling is based on the formation of noble morals as the core goal of education; second, placing monotheism as the main foundation in guiding individuals towards happiness in the world and the hereafter. These two characteristics show that Islamic Educational Counseling not only plays a role in solving psychological problems, but also in forming the religious personality of students as a whole. The implication of this finding is the need for Islamic educational institutions to integrate the Islamic Counseling approach into the curriculum and guidance services systematically.